The Analytic Valuation of American Options - Kim, In Joon (Review of Financial Studies, 1990)
No analytic solution exists for the valuation of American options written on futures contracts and foreign currencies for which early exercise may be optimal. This article formulates the American option valuation problem in economically and mathematically meaningful ways. This enables us to derive valuation formulas for American options. The properties associated with the optimal exercise boundary are examined, and a numerical technique to implement the valuation formulas is presented.